O papel do programa de aquisição de alimentos – PAA - para o fortalecimento da agricultura familiar: o caso da Cooperativa da Agricultura Familiar Integrada – COOPAFI - de Capanema, PR - Silva, Vilmar da (2013)
In a country where family farming is historically treated as ‘the ugly duckling’, and public policy generally directed to agriculture employer in the production of agricultural commodities it is created by the Federal Government in 2003, the Food Acquisition Program – FAP (PAA), which has embraced as one of its objectives ‘Strengthening Family Farming’. With this idea in mind, the quest about reification of this objective caused the interest in seeking data that could contribute to the understanding of the way the FAP (PAA) reaches the farmers, both in economic and social context. Thus, searching for an answer about what is the program role on strengthening family farming and considering that the strengthening of agriculture also occurs according to extensive bibliography already produced from the organization of farmers into associations and cooperatives, a case study was conducted at the Family Farming Cooperative Integrated - Coopafi – Capanema, it was chosen for being result of the first marketing cooperative of family farms in the Southwest Region of Paraná, Cooperfac - Family Agriculture Cooperative of Capanema. In this sense the dissertation discusses how marketing strategies of family farming emerge in the markets, both institutional and private. The main objective of this work is to identify the role of FAP (PAA) to strengthen family agriculture due to the strengthening of relations between the farmers and the institutional market. For this reason, two hypotheses guide the research: the first asserts that the action of Public Policy – FAP (PAA) - accomplishes the objectives with what have been proposed and has a significant importance on strengthening family farming and sustainable rural development. The second hypothesis refers to the fact that the actors involved, family farmers and cooperative leaders, in the whole process of marketing the FAP (PAA) are aware of the importance of Public Policy in improving the socioeconomic conditions of Family Farmers and the society in which they are inserted. The extend of these issues asserts the choice of performing a case study and the use of techniques of quantitative and qualitative research. Thus, the methodological procedures relating to the application of a standardized form, semi-structured interview and direct observation, besides the use of secondary data. In summary, the survey results confirm, in part, the initial hypotheses. First, they demonstrate that the FAP (PAA) strengthens family farms, but with some limitations. At the same time, they highlight how the process of commercialization via FAP (PAA) modified the mode of production and the farmer's family relationship with the market, demonstrating the perception of farmers related to the importance of FAP (PAA) and associations for sustainable development.